2017
DOI: 10.1371/journal.pcbi.1005400
|View full text |Cite
|
Sign up to set email alerts
|

The role of the Hes1 crosstalk hub in Notch-Wnt interactions of the intestinal crypt

Abstract: The Notch pathway plays a vital role in determining whether cells in the intestinal epithelium adopt a secretory or an absorptive phenotype. Cell fate specification is coordinated via Notch’s interaction with the canonical Wnt pathway. Here, we propose a new mathematical model of the Notch and Wnt pathways, in which the Hes1 promoter acts as a hub for pathway crosstalk. Computational simulations of the model can assist in understanding how healthy intestinal tissue is maintained, and predict the likely consequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 128 publications
(208 reference statements)
1
33
0
Order By: Relevance
“…[38][39][40][41] The results obtained in this study show that indomethacin, juglone, and cotreatment of these two drugs, exhibits their action, presumably, by downregulating the inflammatory mediators, inhibiting the activation of antiapoptotic molecules and increasing the levels of proapoptotic molecules to induce apoptosis in HT29 cells. [45] It has been previously reported that the overexpression of Notch signaling alone does not contribute to cancer initiation; however, cross-talk between the Wnt and Notch pathways is known to increase the risk of cancer initiation [42,46] ; while, their interaction with PPARγ decreases the risk of oncogenic upregulation upon its activation by an external drug as a ligand. [42,43] Activation of the Wnt signaling pathway leads to aberrant translocation of β-catenin and initiating tumor progression through the upregulation of its target genes such as cyclin D1, c-jun, c-Myc, and fra-1.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41] The results obtained in this study show that indomethacin, juglone, and cotreatment of these two drugs, exhibits their action, presumably, by downregulating the inflammatory mediators, inhibiting the activation of antiapoptotic molecules and increasing the levels of proapoptotic molecules to induce apoptosis in HT29 cells. [45] It has been previously reported that the overexpression of Notch signaling alone does not contribute to cancer initiation; however, cross-talk between the Wnt and Notch pathways is known to increase the risk of cancer initiation [42,46] ; while, their interaction with PPARγ decreases the risk of oncogenic upregulation upon its activation by an external drug as a ligand. [42,43] Activation of the Wnt signaling pathway leads to aberrant translocation of β-catenin and initiating tumor progression through the upregulation of its target genes such as cyclin D1, c-jun, c-Myc, and fra-1.…”
Section: Discussionmentioning
confidence: 99%
“…We observed down-regulation of HES1 by psychological stress level of glucocorticoids, HES1 deficiency resulted increased goblet cell population, altered colon crypts morphology and impaired gut homeostasis which conform to the mathematical model [5, 9, 59]. These features indicate that the HES1 promoter is also a potential crosstalk hub of Notch-GC interactions in colon crypts [5, 60]. The levels of these opposite transcription factors are coupled with tight junction protein levels.…”
Section: Data Notesmentioning
confidence: 52%
“…1,11). Recent mathematical models confirmed that HES1 promoter is the crosstalk hub in Notch-Wnt interactions of the intestinal crypts, our recent study also suggested that physiological glucocorticoid (GC) signal can affect HES1 expression via HES1 promoter negative glucocorticoid response element (GRE) [5, 59, 60]. We observed down-regulation of HES1 by psychological stress level of glucocorticoids, HES1 deficiency resulted increased goblet cell population, altered colon crypts morphology and impaired gut homeostasis which conform to the mathematical model [5, 9, 59].…”
Section: Data Notesmentioning
confidence: 98%
“…There are, however, many detailed mathematical models of ISCs, some of which have been developed and validated against experimental data (34)(35)(36)(37). Additional models can be found in the reviews by Kershaw Compared with these models, our model is purposely simplified to unravel the complex dynamics that govern cell proliferation during differentiation.…”
Section: Discussionmentioning
confidence: 99%